1996
DOI: 10.1002/(sici)1096-8628(19960726)67:4<401::aid-ajmg14>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutation of the cholecystokinin B receptor gene: Lack of association with panic disorder

Abstract: Cholecystokinin tetrapeptide (CCK4) is known to induce panic attacks in patients with panic disorder at a lower dose than in normal controls. Therefore, the cholecystokinin B (CCKB) receptor gene is a candidate gene for panic disorder. We searched for mutations in the CCKB gene in 22 probands of panic disorder pedigrees, using single-strand conformation polymorphism (SSCP) analysis. Two polymorphisms were detected. A polymorphism in an intron (2491 C-->A) between exons 4 and 5 was observed in 10 of 22 probands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Two association studies of a polymorphism in the promoter region of the CCK gene did not find consistent evidence of an association with panic disorder [40,41]. Although no association was seen in a small case-control study of the CCK-B receptor [42], a subsequent study [40] did observe evidence of association in a sample of ethnically matched cases and controls.…”
Section: Molecular Studiesmentioning
confidence: 96%
“…Two association studies of a polymorphism in the promoter region of the CCK gene did not find consistent evidence of an association with panic disorder [40,41]. Although no association was seen in a small case-control study of the CCK-B receptor [42], a subsequent study [40] did observe evidence of association in a sample of ethnically matched cases and controls.…”
Section: Molecular Studiesmentioning
confidence: 96%
“…A linkage study by Gelernter et al [174] suggested a risk locus at marker CCKBR on chromosome 11p with a LOD score of 2.01. Kato et al [175] were the first to identify a CCKBR missense mutation in exon 2 (1550G/A) and an intron 4 variation (2491C/A) by means of SSCP analysis in patients with PD, which, however, did not show association with the disease in a sample of 34 patients. Another group could confirm non-association of 1550G/A and 2491C/A as well as of two further CCKBR SNPs (1962T/C, 1985G/A) in an independent sample of 91 Japanese patients with PD.…”
Section: Cck-2r Gene (Cckbr; Chromosome 11p154)mentioning
confidence: 99%
“…Initial analyses of a complete genome scan for panic disorder did not reveal evidence of significant linkage [Knowles et al, 1998]. In candidate gene studies, a variety of neurotransmitter and neuropeptide receptor genes have been tested and failed to show linkage to or association with the panic disorder phenotype [Crowe et al, 1987, 1997; Mutchler et al, 1990; Wang et al, 1992; Crawford et al, 1995; Kato et al, 1996; Ohara et al, 1996; Steinlein et al, 1997]. More recently, several nominally significant associations have been reported, though none have been established [Deckert et al, 1998, 1999; Rowe et al, 1998; Wang et al, 1998; Kennedy et al, 1999; Nakamura et al, 1999].…”
Section: Introductionmentioning
confidence: 99%